Independence, Professional Skepticism, And Audit Quality: The Moderating Role Of Audit Fees - Juliyanti Sidik Tjan; Muslim, Muslim; Andriani Alimin; Muh Yamin Noch; Yaya Sonjaya (Jurnal Akuntansi, 2024)
This research investigates the impact of auditor independence and professional scepticism on audit quality, focusing on audit fees as a moderating factor in Makassar City's public accounting firms. The study employs census sampling, involving 39 auditors from eight Makassar-based public accounting firms. Hypotheses are tested using multiple linear regression via Smart PLS 3.0 software, complemented by descriptive statistical tests. The research also conducts assessments, including convergent validity, discriminant validity, composite reliability, and inner model evaluations. Results indicate that auditor independence and professional scepticism positively and significantly affect audit quality. As a moderating variable, audit fees also positively and significantly impact audit quality. These findings offer public accounting firms valuable insights, emphasising the need to evaluate and potentially adjust their policies proactively. This proactive approach can help mitigate potential risks linked to declining audit quality.